Studi Tentang Hak Asuh Anak Di Bawah Umur Akibat Perceraian Berdasarkan Undang – Undang Nomor 1 Tahun 1974 - Dewi Ratih Kumalasari (JURNAL HUKUM PELITA, 2025)
Marriage is a legal and social bond between two individuals that can be carried out by every human being based on an agreement to live together as a couple. However, a marriage that is expected to always live together until the end of life, is not as young as imagined. Some people choose to end their marriage because of quarrels or incompatibility between each other, it can be called divorce. Divorce that already has children, especially minors, will be an important impact in a divorce process is about child custody. Every parent, both mother and father who divorces, will fight for custody of their child in order to get full responsibility in caring for and educating the child, and to have the opportunity to be involved in the child's life |after the divorce. |Although custody of the child h|as f|allen on either p|arent, they |also h|ave |an oblig|ation to c|are for |and educ|ate their child. This h|as been regul|ated by leg|al regul|ations in Indonesi|a in L|aw Number 1 of 1974, concerning M|arri|age. By using a research method combining a qualitative descriptive approach with normative juridical procedures obtained from various sources, journal references, as well as opinions from institutions and experts who have authority regarding the study of custody of minors due to divorce